LINGUOAXIOLOGICAL FEATURES OF PSYCHOLOGICAL TERMS IN ENGLISH AND UZBEK LITERARY TEXTS - Khudoymurodova Mukhayyo Khayrullo kizi (Modern American Journals, 2025)
This article explores the linguoaxiological characteristics of psychological terminology as reflected in English and Uzbek literary texts. The research highlights the interrelation between language, cognition, and value systems, demonstrating that psychological terminology in literary discourse not only functions as a tool for describing emotional and mental states but also as a reflection of national mentality and worldview. By employing comparative and descriptive linguistic methods, the study identifies similarities and differences in the use of psychological terms across English and Uzbek literary texts.
Keywords: Linguoaxiology; psychological terminology; literary discourse; emotional semantics; cultural values; English literature; Uzbek literature.